Pengembangan Bahan Ajar Elektronik Kurikulum 2013 Menggunakan Android Untuk Meningkatkan Keterampilan Menyimak: Penelitian dan Pengembangan di MA Muhammadiyah Sumberrejo Bojonegoro - Muh. Zakki Amrulloh; Faruq Abdul Muid (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2021)
This study aimed to development of electronic teaching material using android. The requirement analysis finds that Listening electronic materials are rarely available in Madrasah Aliyah Arabic books. In addition, students’ interest in Arabic listening learning is low. The research method uses in this study is Research and Development (R & D) method by Pretest-Postest Control Group Design. The steps in the study are potential and problem analysis, data collection, product design, design validation by the media experts and the material experts, design revisions; product testing to grade X students of MA Muhammadiyah 1 Sumberrejo Bojonegoro where the number of the experimental class students are 20. The developed medium is consisted of 6 Andoid Applications in accordance with the number of Arabic material chapters in class X. Based on validation results the developed medium belongs to the category worthy to be used as a medium of Arabic listening learning. The hypothesis result which is analysed by t-test shows that the value of significance = 0.012 < from 0.05 And t-count (2,644) is greater than t-table (1,686). It means Ha is accepted or the average score of experimental class (73, 75) is higher than the average score of control class (64, 25). It can be said that the experimental class has a significant different to the control group.